Peran Guru Kelas Menanamkan Pendidikan Karakter Melalui Bimbingan Konseling Sosial - Wahyu Setyaningrum; Fitrotun Ni'mah; Nur Khikmah (Institut Agama Islam Negeri Curup, 2023)
The purpose of this study was to determine the role of the classroom teacher in instilling character education at the elementary school level through counseling. The method used is descriptive qualitative research approach. The results of the study show that first, at the Al Azhar Islamic Elementary School, monitoring of student’s uses the habit of using parents to send photos, for example photos of children praying at home and doing assignments according to the goggle classroom. In this way, students will be more focused on learning and worship. Second, at the Al Azhar Islamic Elementary School 29 BSB Semarang City, every day the teacher records for children who violate the rules and records the orderly children to fill in the values of Core Competency I and Core Competency 2. Third, at Al Azhar Islamic Elementary School 29 BSB Kota Semarang the way the teacher anticipates unfavorable conditions according to external factors that can affect the character of students is by holding religious coaching activities at Al Azhar Islamic Elementary School holding puberty activities for students who are menstruating. Regarding motivation that aims to direct students to good things. For class 6 specific learning activities there is a specific plan for building school character calling resource persons to fill in the program. The contribution in this study is expected to increase knowledge related to social counseling at the elementary school level.